2008
DOI: 10.1007/s00464-008-9969-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of technical proficiency in performing needle-knife precut papillotomy

Abstract: Whereas the initial success rate for NKPP can increase with procedural experience, the complication rate does not seem to decrease. Furthermore, the need for NKPP does not appear to decrease with increasing endoscopic retrograde cholangiopancreatography (ERCP) experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…Precut papillotomy increases significantly the success of selective biliary cannulation. In this study, the overall rate on biliary cannulation, before and after precutting, was similar to other series [8,9,[15][16][17]. We obtained an overall biliary cannulation rate of 95%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Precut papillotomy increases significantly the success of selective biliary cannulation. In this study, the overall rate on biliary cannulation, before and after precutting, was similar to other series [8,9,[15][16][17]. We obtained an overall biliary cannulation rate of 95%.…”
Section: Discussionsupporting
confidence: 86%
“…Overall complication rates were similar in all groups (12,18,20,12, and 14%), with no difference in complication severity. Recently, Fukatsu et al [16] also demonstrated that success and complication rates do not change with increasing experience. Trauma and edema of the papilla because of multiple unsuccessful attempts at biliary cannulation and inadvertent pancreatic cannulation could contribute to the risk of pancreatitis, instead of the precut papillotomy itself.…”
Section: Introductionmentioning
confidence: 95%
“…Even so, the success rate of NKF is still low [8,9]. For another technique, NKPP, only pinkish or dark red bile duct has been mentioned in most literature without more details about the procedure [10]. In our practice, we have improved the operation procedure by combining NKPP and NKF for successful biliary cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…This could increase the proportion of patients with inadvertent injection of contrast to the main pancreatic duct, which is per se a risk factor for post-ERCP pancreatitis, not specifically related to the NKF technique. The results from other studies are diverse, Harewood et al reported that the adverse events did not diminish over time and Fukatsu et al reported an increase from 10 % to 16 % (• " Table 3) [2,11,15,19]. On the other hand, Robinson et al reported a decrease in adverse events over time, which may be explained by the increased use of pancreatic stents in the latter groups (• " Table 3) [16,17,20,21].…”
mentioning
confidence: 98%